2002
DOI: 10.1046/j.1439-0531.2002.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Swim up and Percoll Treatment on Viability and Acrosome Integrity of Frozen–thawed Bull Spermatozoa

Abstract: The aim of this study was to investigate the effect of the swim up and Percoll methods to select frozen-thawed bull spermatozoa with high quality membrane and acrosomal integrity and final concentration. Semen samples from six Holstein-Friesian bulls were examined. The whole experiment was repeated three times. Before and after both treatments, spermatozoa were subjected to a double-staining method and evaluated by brightfield light microscope using 40x dry, or 100x oil immersion objectives. The concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
72
2
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 27 publications
7
72
2
4
Order By: Relevance
“…These observations are in agreement with the previous reports in cattle. It is evident in cattle that 60% to 70% spermatozoa remain viable (Somfai et al, 2002;Nagy et al, 2004), 70% to 80% spermatozoa remain morphologically normal (Somfai et al, 2002;Januskauskas et al, 2005) and 50% to 80% spermatozoa retain intact acrosome after cryopreservation (Somfai et al, 2002;Nagy et al, 2004). The current study revealed that the trypan blue-Giemsa staining technique can be used efficiently for the simultaneous evaluation of viability, morphological abnormality and acrosomal integrity of mithun spermatozoa.…”
Section: Discussionmentioning
confidence: 61%
“…These observations are in agreement with the previous reports in cattle. It is evident in cattle that 60% to 70% spermatozoa remain viable (Somfai et al, 2002;Nagy et al, 2004), 70% to 80% spermatozoa remain morphologically normal (Somfai et al, 2002;Januskauskas et al, 2005) and 50% to 80% spermatozoa retain intact acrosome after cryopreservation (Somfai et al, 2002;Nagy et al, 2004). The current study revealed that the trypan blue-Giemsa staining technique can be used efficiently for the simultaneous evaluation of viability, morphological abnormality and acrosomal integrity of mithun spermatozoa.…”
Section: Discussionmentioning
confidence: 61%
“…En investigaciones realizadas en bovino con pool de semen, señalan que con SU, la población celular tiene un mayor porcentaje de espermatozoides viables con membrana plasmática intacta, evaluados por HOST comparado con los obtenidos por método de centrifugación por gradiente de densidad como el Percoll® (Mehmood et al). Contrariamente, Somfai et al (2002) señalan que con Percoll® se obtiene una población espermática de mayor viabilidad comparada con SU. Los resultados obtenidos respecto a este parámetro confirman la variabilidad de los espermatozoides de equino y la capacidad de los diferentes métodos en seleccionar los viables con membrana plasmática intacta.…”
Section: Discussionunclassified
“…In contrast, Kőhn et al (1997) found comparable results of viability as well as acrosome reaction rate with human sperm. Although several authors have studied bovine sperm (Didion et al, 1989;Way et al, 1995;Somfai et al, 2002), no direct comparison of these two techniques has been made. In studies with bovine sperm (Didion et al, 1989;Way et al, 1995), ejaculated rather than frozenthawed spermatozoa were tested.…”
mentioning
confidence: 99%